Importing and Firm Productivity in Ethiopian Manufacturing - Abreha, Kaleb Girma (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper investigates the causal relationship between importing and firm productivity. Using a rich dataset from Ethiopian manufacturing over the period 1996–2011, I find that most firms rely on production inputs from the world market. These firms are better performing as shown by significant, economically large import premia. I also find strong evidence of self-selection of more productive firms into importing which is indicative of sizable import market entry costs. To examine the causal effect of importing on firm productivity, I use a model in which the static and dynamic effects of importing are separately estimated. The estimation results provide support to learning-by-importing. However, the productivity gains are small in size compared to similar findings in other studies. I provide some evidence in support of firms’ limited absorptive capacity in explaining the small productivity gains.